Biology Learning in the AI Era: Investigating the Effects of Digital Fatigue, Cognitive Load, and Moral Reasoning on Student Outcomes - Rizky Aprilliani Nurdin; Andi Mu'nisa; Asham Bin Jamaluddin; Firdaus Daud; Ismail (International Journal of Educational Practice and Policy, 2026)
This study aimed to examine the effects of digital fatigue, cognitive load, and moral reasoning on biology knowledge and biology attitudes, as well as the effect of biology knowledge on biology attitudes among senior high school students in Makassar City during the era of Artificial Intelligence (AI). A cross-sectional design was employed involving 500 students from 10 senior high schools in Makassar City. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results revealed that digital fatigue, cognitive load, and moral reasoning had positive and significant effects on both biology knowledge and biology attitudes (p < 0.05). Biology knowledge also had a positive and significant effect on biology attitudes (β = 0.386, p < 0.05). The R² values indicated that the model explained 69.3% of the variance in biology knowledge and 73.9% of the variance in biology attitudes. These findings suggest that cognitive factors, moral reasoning, and digital learning experiences play important roles in enhancing biology knowledge and shaping students’ attitudes toward biology in the AI era.